Enhancement of antifungal activity and transdermal delivery of 5-flucytosine via tailored spanlastic nanovesicles: statistical optimization, in-vitro characterization, and in-vivo biodistribution study - Safhi, Awaji Y.; Naveen, Nimbagal Raghavendra; Rolla, Krishna Jayanth; Bhavani, Penmetsa Durga; Kurakula, Mallesh; Hosny, Khaled M.; Abualsunun, Walaa A.; Alissa, Mohammed; Alsalhi, Abdullah; Alahmadi, Amerh Aiad; Zoghebi, Khalid; Halwaani, Abdulrahman Sindam; et al. (Frontiers in Pharmacology, 2023)
Aim and Bbackground: This current study aimed to load 5-fFlucytosine (5-FCY) into spanlastic nanovesicles (SPLNs) to make them drug more efficient as an antifungal and also to load them 5-FCY into a hydrogel that wouldwhich allows for enhanced transdermal permeation, and improved patient compliance.The preparation of 5-FCY-SPLNs was optimized by using a central composite design that consideredtook into account Sspan 60 (X1) and the edge activator (Tween 80 -(X2) as process variables in achieving the desired particle size (PS) and entrapment efficiency (EE).Using the desirability method, Aa formulation containingwith Span 60 of 295.79 mg of Span 60 and Tween 80 of 120.00 mg of Tween 80 was found to can meet the prerequisites of the desirability method. The optimized 5-FCY-SPLN formulation was further formulated into a spanlastics gels (SPG) so that thefor topical delivery of 5-FCY-SPLNs could be delivered topically and characterized in terms offor various parameters.As required, the SPG hadshowed the desired elasticity, which can be credited to the physical characteristics of SPLNs. An eEx-vivo permeation study showed that the greatest amount of 5-FCYmost drug penetrated per unit area (Q) (mg/cm 2 ) over time and the average flux (J) (mg/cm 2 /h) was at the end of 24 hours. Drug release studies have showedn that the drug continued to be released until the end of 24 hours and that the pattern wasof further correlateds with an ex-vivo permeation and distribution study. The biodistribution study showed that the 99mTc-labeled SFG that permeated through the skin had a steadier release pattern, a longer duration of circulation duration with pulsatile behavior in the blood, and higher levels in the bloodstream than the oral 99mTc-SPNLs. ThereforeSo, a 5-FCY transdermal hydrogel could be seen as a possibly be a long-acting formula for maintenance treatment that could be given in smaller doses and less often than the oral formula.